Determinants of Employment Stability in Russia and Eastern Germany: A Comparative Analysis of Micro data - КарабчукТатьяна Сергеевна (Journal of Economic Sociology, 2010)
The paper presents a comparative analysis of the employment stability in Russia and Eastern Germany applying a single methodology and comparable micro data sets. In the early 1990s Russia and Eastern Germany went through fundamental changes resulted from the transition from planned to market economy. Despite the fact that each of these countries followed its own way of transformation, the principles of employment have been similar in many ways. Research focuses on a key characteristic of stability/instability of employment. Representative nation-wide data bases (RLMS for Russia and GSEOP for Eastern Germany) provide an opportunity for measurement and econometric analysis. The presented paper reveals and compares main factors of employment instability in Russia, Eastern and Western parts of Germany.